Better Students Ask More Questions.
expand : log (√(ab)/e^2)
1 Answer | add yours
Best answer as selected by question asker.
We have to expand log (sqrt (ab)/e^2). I assume the base of the logarithm here is e.
log(e) [(sqrt (ab)/e^2)]
We use the relations log ab = log a + log b, log a/b = log a - log b and log x^n = n*log x
=> log(e) [sqrt (ab)] - log(e) e^2
=> (1/2)*log(e) [ ab] - 2*log(e) e
=> (1/2)*log(e) a - (1/2)*log(e) b - 2
The required result is (1/2)*log(e) a - (1/2)*log(e) b - 2
Posted by justaguide on February 16, 2011 at 12:21 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.